Conservation in first introns is positively associated with the number of exons within genes and the presence of regulatory epigenetic signals - Park, Seung Gu (BioMed Central, 2014)
BACKGROUND: Genomes of higher eukaryotes have surprisingly long first introns and in some cases, the first introns have been shown to have higher conservation relative to other introns. However, the functional relevance of conserved regions in the first introns is poorly understood. Leveraging the recent ENCODE data, here we assess potential regulatory roles of conserved regions in the first intron of human genes. RESULTS: We first show that relative to other downstream introns, the first introns are enriched for blocks of highly conserved sequences. We also found that the first introns are enriched for several chromatin marks indicative of active regulatory regions and this enrichment of regulatory marks is correlated with enrichment of conserved blocks in the first intron; the enrichments of conservation and regulatory marks in first intron are not entirely explained by a general, albeit variable, bias for certain marks toward the 5’ end of introns. Interestingly, conservation as well as proportions of active regulatory chromatin marks in the first intron of a gene correlates positively with the numbers of exons in the gene but the correlation is significantly weakened in second introns and negligible beyond the second intron. The first intron conservation is also positively correlated with the gene’s expression level in several human tissues. Finally, a gene-wise analysis shows significant enrichments of active chromatin marks in conserved regions of first introns, relative to the conserved regions in other introns of the same gene. CONCLUSIONS: Taken together, our analyses strongly suggest that first introns are enriched for active transcriptional regulatory signals under purifying selection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-526) contains supplementary material, which is available to authorized users.